Mengoptimalkan Motivasi Belajar Siswa: Peran Dukungan Guru dalam Manajemen Pendidikan di SDN 060952 Medan Labuhan - Lisnasari, Srie Faizah; Jainab, Jainab; Datten, Datten; Susanti, Dewi Afriany; Pelista, Pelista (Universitas Quality, 2024)
This study delves into the crucial role of teacher support in enhancing students' learning motivation at State Elementary School 060952 Medan Labuhan. Employing a qualitative research approach, the study incorporates classroom observations, teacher interviews, and content analysis of learning materials at SDN 060952 Medan Labuhan, specifically focusing on class V-A students.The regression analysis reveals a coefficient value of 0.400 for the gender variable, indicating that male students exhibit higher learning motivation than their female counterparts. However, with a p-value of 0.027, the relationship between gender and learning motivation lacks statistical significance. The R-squared value of 0.204 suggests that teacher support can account for 20.4% of the variation in student learning motivation, implying the existence of other influential factors like family dynamics, environment, and individual personalities. Analyzing the histogram, it becomes evident that most students score within the 3.75 - 4.00 range, indicating generally good learning motivation. However, a small percentage falls into the 3.50 - 3.75 range, reflecting lower motivation levels.In conclusion, this research highlights the positive impact of teacher support on student learning motivation. Teachers can bolster motivation by providing attention, appreciation, positive feedback, fostering a pleasant learning environment, and assisting students in overcoming learning challenges.